Position of oral cephalosporins and its fixed-dose combinations in the guideline recommendations for the management of community-acquired infections - Mala Kaneria; Ilambarathi M; Singh, Vishal; Varun N; Rashmi Hegde; Praveen Kamble; Krunal Dalal (Asian Journal of Medical Sciences, 2023)
Community-acquired infections (CAIs) represent a major burden for health-care system. This directly aids the emergence of antibiotic-resistant organisms. India is not immune to it. This review assessed the current guideline recommendations for the usage of oral cephalosporins in the management of common CAIs. The researchers conducted iterative searches in PubMed, SCOPUS, and Google Scholar for published articles using various keywords. The search was conducted in November 2022 and considered articles published till date. Different CAIs are caused by similar organisms, susceptible to first-line antibiotics such as penicillin and cephalosporins. Most of the guidelines recommend the use of oral cephalosporins for the management of the commonly prevalent CAIs. These antibiotics however should be used as a monotherapy and not as fixed-dose combinations (FDCs), as FDCs with oral cephalosporins lack scientific basis and may be detrimental. For burden of CAIs intensified by anti-microbial resistance, guidelines are useful for the management of CAIs to educate the prescribers and preserve currently available antibiotics.